An evaluation of Empty Fruit Bunch (EFB) biochar and EFB compost as growing media for oil palm seedling / Muhammad Syafiq Ahmad Dani - Ahmad Dani, Muhammad Syafiq (Faculty of Plantation and Agrotechnology, 2018)
Empty Fruit Bunch (EFB) is usually use as mulching material in oil palm plantation sector for new transplanted seedling since it shows good characteristic in conserve soil moisture and contain high nutrient. The nutrient content has been improved in compost process through anaerobic respiration and biochar process through pyrolysis. This advantages has been seen have a potential to be growing media for oil palm seedling in pre-nursery. This study was aim to evaluate the suitability of EFB compost and EFB biochar as growing media and to determine the optimum ratio of EFB compost and EFB biochar as a growing media. This study was carried out by applied different ratio of EFB biochar and EFB compost (0:0, 1:4, 2:3, 3:2, 4:1, 5:0) in pre-nursery oil palm seedling stage. Growth performance of oil palm seedling were measured on weekly basis while soil properties and nutrient content in plant tissues were analysed at the end of experiment. Result showed there were no significant different in growth performance for 10 weeks through statistical analysis but T1 (1:4) was highest growth performance determined through field observation. The soil properties showed pH was improved from acidic (pH 4.0) to desired pH for plant uptake by adding EFB compost and EFB biochar. The available of P, K, Ca and Mg increased by adding EFB compost. The soil properties showed available P, K, Ca and Mg was high for T1 (1:4) and pH for T1 was optimum range (pH 6.0-7.0), in the same time indicate T1 was the most optimum ratio as growing media.